Guitar audio amplifier / Muhammad Syafiq Mohd Hafizi & Sukri Mohd Nasir - Mohd Hafizi, Muhammad Syafiq; Mohd Nasir, Sukri (2015)
Guitar audio amplifier is project related with electronic amplification system with combination of basic electronic component such as resistor, capacitor, diode, switch and transistor. Besides, this project also uses Integrated Circuit (IC) for its amplifier component. This project was proposed to design simple guitar amplifier that consist of three main part of circuit, pre amplifier circuit, power supply circuit and power amplifier circuit. Study show that this guitar amplifier should be able to produce sound or actually amplify it by choosing whether bass, treble or trouble.